Efek Seduhan Jahe Sebagai Anti Muntah Pada Perempuan Hamil Trimester Pertama - Yanuaringsih, Galuh Pradian; Nasution, Ade Saputra; Aminah, Siti (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Pregnancy is a process awaited by the family, but in the process of young pregnancy or the first trimester, there are physical, psychological and hormonal changes that cause symptoms of emesis gravidarum or nausea vomiting that can interfere with and endanger the health of pregnant women if left unchecked such as weakness, lethargy, fluid loss body and can cause dehydration and can even endanger the growth and development of the fetus. Ginger which is well known for cooking spices in Indonesia has other benefits such as reducing nausea and vomiting in pregnant women, where ginger is antiemetic. This study aims to look at the effectiveness of steeping ginger as an anti-emetic in first-trimester pregnant women. This study used a pre-experiment with a pre-test post-test design approach which had 16 samples taken by accidental sampling and the data were analyzed using the Wilcoxon test. The results showed that before treatment, the average vomiting was 3.87, while after treatment, the average vomiting was 1.19, meaning that there was a decrease in nausea and vomiting after treatment with steeping ginger for seven days.